Does geographic targeting of nutrition interventions make sense in cities?: evidence from Abidjan and Accra - Morris, Saul Sutkover; Levin, Carol E.; Armar-Klemesu, Margaret; Maxwell, Daniel G.; Ruel, Marie T. (International Food Policy Research Institute, 1999)
Although most developing country cities are characterized by pockets of substandard housing and inadequate service provision, it is not known to what degree low incomes and malnutrition are confined to specific neighborhoods. This analysis uses representative household surveys of Abidjan and Accra to quantify small-area clustering in service provision, demographic characteristics, consumption, and nutrition. Both cities showed significant clustering in housing conditions but not in nutrition, while income was clustered in Abidjan, but less so in Accra. This suggests that neighborhood targeting of poverty-alleviation or nutrition interventions in these and similar cities could lead to undercoverage of the truly needy.